2022
DOI: 10.3390/nu14173489
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sociodemographic Factors, Lifestyle, and Risk Perception on Dietary Patterns in Pregnant Women Living in Highly Contaminated Areas: Data from the NEHO Birth Cohort

Abstract: During pregnancy, maternal nutrition and lifestyle play a critical role in influencing fetal development and newborn health outcomes. The aim of this study is to investigate the factors influencing the adherence to dietary patterns in pregnant women living in highly contaminated areas, and whether women with higher environmental risk perception manifest different nutritional behaviors during pregnancy. Food consumption data on 816 pregnant women from the Neonatal Environment and Health Outcomes (NEHO) resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…Interestingly, we found that the H-Exp cluster was composed of a higher percentage of women with higher educational levels: this result is in agreement with our recent study (Ruggieri et al, 2022) showing that, in pregnant women, a higher educational stage enhances attention toward a “healthy” dietary pattern characterised by higher fish and vegetable consumption. Nevertheless, a similar diet, in a highly contaminated area, could produce a counterintuitive effect with a higher risk for exposure to environmental pollutants.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that the H-Exp cluster was composed of a higher percentage of women with higher educational levels: this result is in agreement with our recent study (Ruggieri et al, 2022) showing that, in pregnant women, a higher educational stage enhances attention toward a “healthy” dietary pattern characterised by higher fish and vegetable consumption. Nevertheless, a similar diet, in a highly contaminated area, could produce a counterintuitive effect with a higher risk for exposure to environmental pollutants.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that the H-Exp cluster was composed of a higher percentage of women with higher educational level: this result is in agreement with our recent study 27 showing that, in pregnant women, higher educational stage and older age appear to enhance attention toward a “healthy” dietary pattern characterised by higher fish (bluefish in particular) and vegetable consumption. Nevertheless, a similar diet, in a highly contaminated area, could produce a counterintuitive effect with a higher risk for exposure to environmental pollutants.…”
Section: Discussionsupporting
confidence: 93%
“…Between January 2018 and January 2020, the NEHO cohort enrolled 561 pregnant women living in the NPCS of Priolo and in Local Reference Areas (LRAs) located outside the NPCS boundaries (see Supplementary Material , Table A1 ) but characterised by similar socio-demographic features. For the present study, 161 women were randomly selected from the NEHO birth cohort 27 , 85 residing in the NPCS and 76 residing in LRAs: no significant difference was found between the selected sample and the whole birth cohort in Priolo area, with the exception of the numbers of previous pregnancies ( Supplementary Material , Table A2 ). Briefly, after reading a detailed information sheet, all the participants, during their last trimester of pregnancy, were required to sign a consent form confirming their understanding of the project’s aim.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, it was observed that pregnant women with fewer years of education had poorer-quality diets with high sugar consumption and a minimal intake of fruits, meats, and fibre [ 21 ]. In contrast, studies have indicated that pregnant women with higher educational levels show a higher consumption of healthy foods [ 29 , 30 ]. These results suggest an association among educational level, family income, and dietary pattern.…”
Section: Discussionmentioning
confidence: 99%